2003
DOI: 10.1038/sj.jhh.1001630
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the angiotensinogen gene and the outcome of microalbuminuria in essential hypertension: a 3-year follow-up study

Abstract: Background: The objective of this study was to analyse the relationship of polymorphisms of the angiotensinogen (AGT) gene with the changes in microalbuminuria during 3 years of antihypertensive treatment in a group of young adults with essential hypertension. Methods: Essential hypertensives, less than 50 years old, never previously treated with antihypertensive drugs and in the absence of diabetes mellitus were included. After the initial evaluation, patients were treated using only nonpharmacological measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
6
2
Order By: Relevance
“…Although no significant differences in genotypes for either polymorphism were observed between patients with or without microalbuminuria, the A-6G polymorphism seems to influence the risk of new-onset microalbuminuria in a 3-year follow-up study [51]. In this case, the development of microalbuminuria was linked to the changes in fasting glucose and weight [51,52], a previously described association with M235T. In the study performed by Pontremoli et al [53], patients carrying the allele D in ECA, T in AGT and C in AT 1 R have higher early organ damage as compared to carriers of the other alleles of the polymorphisms studied.…”
Section: Renin-angiotensin-aldosterone Systemcontrasting
confidence: 46%
See 2 more Smart Citations
“…Although no significant differences in genotypes for either polymorphism were observed between patients with or without microalbuminuria, the A-6G polymorphism seems to influence the risk of new-onset microalbuminuria in a 3-year follow-up study [51]. In this case, the development of microalbuminuria was linked to the changes in fasting glucose and weight [51,52], a previously described association with M235T. In the study performed by Pontremoli et al [53], patients carrying the allele D in ECA, T in AGT and C in AT 1 R have higher early organ damage as compared to carriers of the other alleles of the polymorphisms studied.…”
Section: Renin-angiotensin-aldosterone Systemcontrasting
confidence: 46%
“…Although no significant differences in genotypes for either polymorphism were observed between patients with or without microalbuminuria, the A-6G polymorphism seems to influence the risk of new-onset microalbuminuria in a 3-year follow-up study [51]. In this case, the development of microalbuminuria was linked to the changes in fasting glucose and weight [51,52], a previously described association with M235T.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 76%
See 1 more Smart Citation
“…Marin et al have very recently reported, that patients with the AA genotype of A-6GAGT genpolymorphism are possibly resistant to reduction of MAU by antihypertensive treatment [34]. It could be speculated that this could be a possible explanation for patients in whom a normalization of MAU in our study could not be achieved.…”
Section: Discussionmentioning
confidence: 82%
“…The AA-6 genotype of the angiotensinogen gene seemed to influence the outcome of microalbuminuria [68]. Despite a larger decrease in DBP among subjects carrying this genotype as compared to the other genotypes, a lower rate of patients with decreasing microalbuminuria and a higher UAE slope over time were observed in homozygotes for the A-6 allele.…”
Section: Geneticsmentioning
confidence: 86%